Hubungan Kompensasi dengan Kinerja Karyawan di VICO Indonesia Company Muara Badak Kalimantan Timur - Hertati, Diana (Universitas Brawijaya, Indonesia, 2009)
The purpose of this research is to know relation compensationÂ with employees performance in VICO Indonesia of Company Estuary Rhinoceros of Kalimantan East This Research represent research of asosiatif, representing research with aim to know relationbetween two variable or more. Variable - variable in this research is compensation variable as independent variable and employees performance variable as variable dependent. In this research use primary data obtained from quesioner answer responder as data and sample of secondary obtained from document data in VICO Indonesia of Company Estuary Rhinoceros of Kalimantan East which is relation with research variable Technique analyse data use correlation analysis method of Spearman Rank for know relation between research variable and use test of t to test research hypothesis. Result of research can concluded that compensation in VICO Indonesia of Company Estuary Rhinoceros of Kalimantan East can influence its employees performance.